Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/jac5.1405
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating outcomes of a clinical pharmacist medication management program in a multidisciplinary practice for outpatient buprenorphine treatment of opioid use disorder

Abstract: IntroductionTreatment with medications such as buprenorphine has been shown to improve outcomes of patients with opioid use disorder (OUD); however, there is still potential to optimize care. Clinical pharmacists may benefit OUD patient treatment by making individualized medication recommendations and enhancing care as part of a multidisciplinary team. This study evaluates a novel outpatient practice model that incorporates pharmacists to manage OUD patients.MethodsA multi‐center retrospective study compared o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 26 publications
(26 reference statements)
3
13
0
Order By: Relevance
“…Mattle et al reported 185 medication interventions at 232 initial and follow‐up visits in an outpatient buprenorphine practice setting, which translated to 0.8 interventions per encounter and was consistent with the number of MTPs identified per visit in this study 15 . At the follow‐up visits of this study, 54/201 MTPs (27%) were marked as “resolved.” Other MTPs may have been resolved, but could not be verified due to a lack of client follow‐up to confirm.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Mattle et al reported 185 medication interventions at 232 initial and follow‐up visits in an outpatient buprenorphine practice setting, which translated to 0.8 interventions per encounter and was consistent with the number of MTPs identified per visit in this study 15 . At the follow‐up visits of this study, 54/201 MTPs (27%) were marked as “resolved.” Other MTPs may have been resolved, but could not be verified due to a lack of client follow‐up to confirm.…”
Section: Discussionsupporting
confidence: 83%
“…In another study in a community setting, patients who received medication therapy management intervention had a lower rate of continued opioid misuse at 3 months, and better pain and depression scores 18 . For outpatient buprenorphine treatment, participants receiving multidisciplinary practice with clinical pharmacists had fewer opioid relapse months 15 . Delivering comprehensive medication management (CMM) services utilizing a patient‐centered approach to optimize treatment is a role that pharmacists can take to improve health outcomes given that patients with SUD usually have co‐occurring mental illnesses or other comorbidities.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Patients were evaluated in-person by a pharmacist and recommendations were discussed and communicated contemporaneously with the treating provider by face-to-face conversation, instant message, and/or chart message. 45 It is possible that the recommendation acceptance rate in the present study may have improved synergistically with direct patient contact and concurrent provider communication.…”
Section: Demographic Characteristics Are Given Inmentioning
confidence: 83%
“…Interestingly, a previous study conducted at the same outpatient neurology center as the present study evaluated outcomes of a clinical program which made use of pharmacists who were physically embedded within a psychiatry practice and found that 89% of medication recommendations were accepted by treating providers. Patients were evaluated in‐person by a pharmacist and recommendations were discussed and communicated contemporaneously with the treating provider by face‐to‐face conversation, instant message, and/or chart message 45 . It is possible that the recommendation acceptance rate in the present study may have improved synergistically with direct patient contact and concurrent provider communication.…”
Section: Discussionmentioning
confidence: 96%